Analisis Willingness To Pay (Wtp) Pengunjung Taman Hewan Di Kota Pematangsiantar Pasca Pandemi Covid19 - Fariaman Purba; Darwin Damanik (Universitas Katolik Widya Karya Malang, 2023)
This study aims to analyze the willingness to pay visitors to the Pematangsiantar City Animal Park and the factors that influence the WTP of the Pematangsiantar City Animal Park. For the research, a sample of 100 people was taken, the sampling was carried out with purposive sampling technique. Sampling of 100 people is considered sufficient considering the population which is the object of research is considered homogeneous. The method used in this study using the TCM model, then continued with multiple regression analysis. The results showed that the average value of the wellingness to pay (WTP) of tourists at the Pematang Siantar Animal Park Tourism Object was Rp. 10,185, -. And the factors that can affect the willingness to pay (WTP) of the Pematang Siantar Animal Park Tourism Object are income, education, travel time, and travel costs have a positive and significant value on the willingness to pay (WTP) of the Pematang Siantar Animal Park Tourism Object.